Possible Involvement of Endothelin Peptides and L-Arginine-Nitric Oxide Pathway on the Effect of Endotoxin in the Rabbit Isolated Perfused Kidney - K. Özsan; R. K. Türker; Z. S. Ercan (Mediators of Inflammation)
Escherichia coli endotoxin (LPS) when infused through the renal artery of the rabbit isolated perfused kidney prepared as constant pressure mode, caused a decrease in flow rate and kidney weight indicating its primary vasoconstrictor effect. This effect was predominant in kidneys from rabbits pretreated with LPS. Endothelin-1 at a concentration of 10−10 M and big endothelin-1 at a concentration of 10−8 M produced equal vasoconstrictor effects in kidney. Addition of endotheHn converting enzyme inhibitor, phosphoramidon, to the perfusion medium at a concentration of 10−6 M caused a reduction in the effects of both LPS and big ET-1 without altering the vasoconstrictor effect of ETol. However, addition of methylene blue (10−5 M), a soluble guanylate cyclase inhibitor and NG-nitro-L-arginine-methyl ester (10−6 M) to the perfusion medium caused a potentiation in the vasoconstrictor effect of LPS. Indomethacin at a concentration of 10−6 M did not alter the effect of LPS. These results were taken as evidence for the participation of endothelin peptides and the L-arginine-nitric oxide pathway in the effect ofLPS in rabbit isolated perfused kidney.